RESPONS TANAMAN KUBIS BUNGA (Brassica oleracea) TERHADAP PEMBERIAN PUPUK MULTI KP PADA ULTISOL: Response of Cauliflower (Brassica oleracea) to Multi KP Fertilizer on Ultisol - Winarti, Sih; Alpian, Alpian; Jaya, Herry Palangka; Suriani, Merti (Fakultas Pertanian Universitas Palangka Raya, 2023)
ABSTRACT Cauliflower are very useful for humans, and have high economic value, but their production in Central Kalimantan is still low because they are grown on utisol soils with low fertility. Therefore, optimal management is needed in order to produce well. This study aims to determine the response of cauliflower plants to the application of Multi KP compound fertilizer and determine the optimal dose of fertilizer for growth and yield of flower cabbage plants. Using a completely randomized design with 5 treatments, namely the application of Multi KP fertilizer with doses of 0, 2, 4, 6 and 8 g plants. 1 . The results showed that the dose of Multi KP fertilizer was 4 g plant-1, the best growth and yield were obtained, namely the plants were able to grow taller, the number of leaves was more, and the cauliflower weight was 320 g per plant.